If x 2 − x − 1 is a factor of z x 2 0 + y x 1 9 + 1 then find y
Details and Assumptions
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution . exceptional . And stop resharing it again and again bro.(am i right?)
Log in to reply
I liked it too much
Log in to reply
HAAHAAA i know BTW have you solved this . You should try and you will like it too. (i liked it very much LOL!) And this set too.
Yup, pretty much the same method. Nice solution!
When you applied the "cross multiplication" method, you should have gotten a 1 9 − b 1 9 z = b 2 0 − a 2 0 y = a 2 0 b 1 9 − b 2 0 a 1 9 1 . Then y = a 1 9 b 1 9 ( a − b ) b 2 0 − a 2 0 = a − b a 2 0 − b 2 0 = F 2 0 = 6 7 6 5 .
Log in to reply
Yes you are right Sir , thanks for correcting me
Thanks! I have updated the answer back to 6765.
Sorry about the confusion.
there's a problem
First when i put in -6765 it said the answer is wrong. :(
Log in to reply
@Calvin Lin will help you for marking your answer correct
Cheers @Aneesh Kundu (>‿◠)✌
Did it the same way although mine was a bit longer since I got stuck up at the initial stages.
I am not able to understand this how?
Approximate and true golden spirals. The green spiral is made from quarter-circles tangent to the interior of each square, while the red spiral is a Golden Spiral, a special type of logarithmic spiral. Overlapping portions appear yellow. The length of the side of one square divided by that of the next smaller square is the golden ratio.
( See this
It seems to me, that in the case when not +1 but -1 is in the given polinomial the answer will be -6756. To doublecheck this I simply used the primitive procedure of finding the ratio.
Dear Megh Choksi, I propose you to check you expression for y as a solution of the system of two linear equations. It seems to me, that you were wrong. I am very sorry.
Mr. Megh Choksi, I am sorry, I didn't see Mr. Jon Haussmann's comment, and your answer to him. I was simply dissapointed when my correct answer 6765 was mentioned as incorrect.
Log in to reply
Now your answer is marked correct Sir , don't be dissapointed
How x^2=x+1 then x^20 = 6765x+4181 and x^19 = 4181x+2584. Replacing the espression given found : x(6765z+4181y)+4181z+2584y+1.
We have the zero the expressions " 6765z+4181y" and " 4181z+2584y+1", which brings us y =6765.
Problem Loading...
Note Loading...
Set Loading...
Since x 2 − x − 1 is a factor of the first polynomial p x 1 7 + q x 1 6 + 1 it means that the roots of the first equation are also the roots of the second polynomial.We can solve the first equation by quadratic formula to find :
x 1 = 2 1 + 5 = a , x 2 = 2 1 − 5 = b
f ( x ) = z x 2 0 + y x 1 9 + 1
f ( a ) = z a 2 0 + y a 1 9 + 1
f ( b ) = z b 2 0 + y b 1 9 + 1
Both are linear equations , thus applying cross multiplication method
a 1 9 − b 1 9 z = b 2 0 − a 2 0 y = a 2 0 b 1 9 − b 2 0 a 1 9 1
a 2 0 − b 2 0 y = a 1 9 b 1 9 ( a − b ) 1
Now,
2 1 + 5 × 2 1 − 5 = − 1
a 1 9 b 1 9 = − 1
y = ( a − b ) a 2 0 − b 2 0
F n = φ − ψ φ n − ψ n (where φ = a , ψ = b )
F n = F n − 1 + F n − 2 , F 1 = 1 = F 2
Thus we have to find F 2 0 w h i c h i s e q u a l t o 6 7 6 5
y = 6 7 6 5
F i b o n a c c i S e r i e s − 1 , 1 , 2 , 3 , 5 , 8 , 1 3 , 2 1 , 3 4 . . . . .